2019
DOI: 10.4028/www.scientific.net/kem.803.143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sintering Holding Time on Tetragonal Phase Stability of Yttria Stabilized Zirconia Ceramics

Abstract: In this study, the effect of second step sintering holding time on LTD of 3 mol% yttria tetragonal zirconia polycrystals (3Y-TZP) ceramic was studied. The Zirconia powder was die pressed followed by cold isostatically pressed (CIP) at 200 MPa, and the samples were initially heated to a first step temperature of 1400°C with constant heating rate 10°C/min and the samples were stand still for 1 minute. Then cooled down to the second step temperature of 1200°C and maintained at that temperature for 2 and 10 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The dominant mechanism for frozen grain growth is suppression of grain boundary migration before the second stage of sintering caused by immobilizing the triple-point junctions, due to rapid cooling after first step sintering and densification achieved by grain boundary diffusion (Sutharsini et al, 2018). Then it was found that TSS enhanced the hydrothermal ageing resistance which is consistent with previous work (Sutharsini et al, 2017(Sutharsini et al, , 2018Vignarajah et al, 2019). The interesting observation here is that two step sintering revealed different ageing behaviours for different samples with the same grain size distribution.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The dominant mechanism for frozen grain growth is suppression of grain boundary migration before the second stage of sintering caused by immobilizing the triple-point junctions, due to rapid cooling after first step sintering and densification achieved by grain boundary diffusion (Sutharsini et al, 2018). Then it was found that TSS enhanced the hydrothermal ageing resistance which is consistent with previous work (Sutharsini et al, 2017(Sutharsini et al, , 2018Vignarajah et al, 2019). The interesting observation here is that two step sintering revealed different ageing behaviours for different samples with the same grain size distribution.…”
Section: Discussionsupporting
confidence: 89%
“…The interesting observation here is that two step sintering revealed different ageing behaviours for different samples with the same grain size distribution. In addition, regardless of the same grain size, the tetragonal to monoclinic phase transformation decreased with increasing sintering holding time (Sutharsini et al, 2017(Sutharsini et al, , 2018Vignarajah et al, 2019). To identify the mechanism behind the unique ageing behaviour, the surface yttria concentration of the samples was studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations